Front Cover: Redox‐Active BIAN‐Based Iron Complexes in Catalysis (Eur. J. Inorg. Chem. 30/2022). Issue 30 (22nd September 2022) - Chacon‐Teran, Miguel A.; Findlater, Michael
Abstract : The Front Cover shows some of the key features and benefits of employing BIANs as redox non‐innocent ligands including a chemist with two flasks helping to illustrate just how "simple" BIAN synthesis can be. The ability to use ligands as electron reservoirs capable of storing and releasing electrons on demand in catalysis has helped to unleash an onslaught of 1 st ‐row metal catalysts onto the chemical catalysis community. Armed with non‐innocent ligands, chemists have started developing new mechanisms and transformations of iron‐based complexes. This review describes recent advances in the field of [BIAN‐Fe] chemistry and catalytic applications of such complexes. We wish to thank Adrian Ernesto Pérez for help with the design of the image. More information can be found in the Review by M. A. Chacon‐Teran and M. Findlater .